The Difficulties that face Al-Qalam University College students at the Department of Physical Education during the field application period - Agag, Safa Mandel (International Journal of Psychosocial Rehabilitation, 2020)
Students face applied to through several application period may be scientific or educational or special equipment sports events, squares and other things that stand obstacle to achieving the goal of the field application, so the goal of research to identify the most important data facing the fourth stage students of the Department of Physical Education During the field application period, where the researcher used the descriptive method for its suitability and the nature of the research. As for the research community, it included the fourth stage students, who are (25) students and the prepared questionnaire was used. It consists of 41 paragraphs that were formulated according to five-year method distributed on five axes (sports capabilities, school students, supervision of field training, school administration, field training programs and curriculum), where the questionnaire was codified on the Iraqi environment after conducting validity and reliability and then processing the data statistically. was reached several conclusions , including the lack of harmony between the systematic theoretical and scientific, which negatively affects the students recommended a number of recommendations , including a student among the numbers of teaching methods in academic classes are guaranteed to enable him to overcome obstacles